Pengembangan Lembar Kerja Peserta Didik Berbasis Inkuiri Terbimbing pada Mata Pelajaran Dasar Listrik dan Elektronika - Irfan Efendi; Ahyanuardi Ahyanuardi (Jurnal Pendidikan Teknik Elektro, 2021)
The student worksheet (LKPD) is one of the tools used by educators to deliver learning materials. The background of this research is that the learning process in schools has not been carried out properly, the results of student learning activities are low, so that the objectives of learning are not achieved, this learning outcome depends on the learning process. Things that affect learning activities are LKPD as a tool in practical learning activities. The purpose of this research is to develop LKPD that is suitable for use so that it will improve the quality of the practicum learning process so that student learning outcomes are better. This type of research is Research and Development (R&D) with a 4D development model consisting of Define, Design, Develop and Disseminate. Valid assessment of LKPD is carried out by experts consisting of media experts and material experts, while practicality is assessed by subject teachers and students, then for effectiveness it is seen from the results of practical learning when using guided inquiry-based worksheets. The instrument collects data using a questionnaire. The results of this study obtained that guided inquiry-based worksheets based on media experts were categorized as valid, while the feasibility of the material based on material experts obtained valid categories. Practicality assessments assessed by subject teachers are categorized as very practical, then practicality assessments from students are categorized as very practical. Assessment of the effectiveness of student learning outcomes is categorized as effective. So that the developed LKPD can be used by teachers to convey material in practical learning activities.